1990
DOI: 10.1080/01652176.1990.9694271
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium intoxication in a dog

Abstract: SUMMARY.A two-year-old male Barsoi dog was presented after a two-week period of muscle twitching and convulsions during exercise, which worsened to a state of tetraparesis and coma.Removal of a gastric foreign body, containing aluminium, resolved the presenting signs.Parallel with this clinical recovery the elevated serum levels of aluminium decreased to values of two normal control dogs, suggesting that the neurological signs were due to A l intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Aluminium intoxication has been reported in a dog presenting with muscle twitching, convulsions, tetraparesis and coma which resolved following removal of a gastric foreign body containing aluminium (van Toor et al 1990) (Table 2). Diet has been associated with some types of canine urolithiasis (Osborne et al 1981) and avoidance of dietary silica (a type of silicate) has been recommended to minimise recurrence of silica uroliths (Minnesota Urolith Centre 2020).…”
Section: Adsorbent Claysmentioning
confidence: 99%
“…Aluminium intoxication has been reported in a dog presenting with muscle twitching, convulsions, tetraparesis and coma which resolved following removal of a gastric foreign body containing aluminium (van Toor et al 1990) (Table 2). Diet has been associated with some types of canine urolithiasis (Osborne et al 1981) and avoidance of dietary silica (a type of silicate) has been recommended to minimise recurrence of silica uroliths (Minnesota Urolith Centre 2020).…”
Section: Adsorbent Claysmentioning
confidence: 99%
“…To date, there is no documentation of aluminum toxicity associated with administration of phosphate‐binding agents in dogs with naturally occurring kidney disease. van Toor et al 13 reported a case of aluminum toxicity in a dog after ingestion of an aluminum foreign object. Clinical signs included convulsions and muscle twitching, which resolved gradually after removal of the foreign object.…”
Section: Casementioning
confidence: 99%
“…4,5 Epidemiological investigations in people have identified important therapeutic considerations and prognostic information based upon signalment and presenting clinicopathologic signs. 4,[6][7][8] Literature pertaining to the underlying etiology and outcome of dogs and cats with coma and stupor is scarce, and largely limited to individual case reports [9][10][11][12][13][14][15][16][17][18][19][20][21] and cases indirectly reported as part of larger populations suffering other systemic illness. [22][23][24][25][26][27][28][29] The objective of this study was to summarize the signalment, clinical findings, underlying etiology, and short-term outcome in a large population of dogs and cats presenting with coma and stupor to a multicenter out-of-hours emergency care provider in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Literature pertaining to the underlying etiology and outcome of dogs and cats with coma and stupor is scarce, and largely limited to individual case reports and cases indirectly reported as part of larger populations suffering other systemic illness …”
Section: Introductionmentioning
confidence: 99%